Regional Training and Research Institute for Distance and Open Learning (RETRIDOL) – Commonwealth of Learning Partnership: A 16-year Journey in Pursuit of Opening up Access to Education - Eya, Patrick Eke; Shaibu, Moses Etila; Amini, Clifford Moses (West African Journal of Open and Flexible Learning, 2019)
This paper highlights the importance, successes and challenges of the 16-year partnership of Regional Training and Research Institute for Distance and Open Learning (RETRIDOL) with the Commonwealth of Learning (COL). The paper sees RETRIDOL as the epicentre for the development of capacity in the delivery of Open and Distance Learning in the West African Sub-region. It also posits that the 16 years’ partnership with a leading, globally acclaimed organization that fosters distance and open learning as the panacea for low access to higher education, COL, has been the major factor in the successes RETRIDOL had recorded so far. The paper further suggests that aligning with the COL Strategic Plan, RETRIDOL would make more impact in engaging individual universities in the region in a bid to making a few operate as dual-mode universities, concluding that such efforts will improve access to higher education in Nigeria, and the West African Sub-region (WASR) in general. Résumé : Cet article souligne l'importance, les succès et les défis du partenariat de 16 ans entre le Regional Training and Research Institute for Distance and Open Learning (RETRIDOL) et le Commonwealth of Learning. Le document considère RETRIDOL comme l'épicentre pour le développement des capacités dans la prestation de l'enseignement ouvert et à distance dans la sous-région ouest-africaine. Il postule également que le partenariat de 16 ans avec COL, une organisation de premier plan, de renommée mondiale qui encourage l'apprentissage ouvert et à distance en tant que panacée à un accès limité à l'enseignement supérieur, a été le principal facteur du succès que RETRIDOL a enregistré jusqu'à présent. L’article suggère en outre qu'en s'alignant sur le plan stratégique du COL, RETRIDOL aurait plus d'impact en engageant les universités individuelles de la région dans le but d'en faire fonctionner quelques-unes en double mode, concluant que de tels efforts amélioreront l'accès à l'enseignement supérieur au Nigéria et dans la sous-région ouest-africaine (SROA) en général.